Women's Drug Use in Everyday Life - Eleonorasdotter, Emma (Springer International Publishing : Imprint: Palgrave Macmillan, 2024)
"This book offers a fascinating insight into the everyday lives of women who use drugs in Sweden. Adopting a queer phenomenological perspective, Dr Eleonorasdotter brings a fresh perspective to debates about drug use and notions of 'harm'. Well-researched and written, the book engages with gendered, classed and stigmatising constructions of women who use drugs represented in policy and practice. We are encouraged to think about what it means to be a woman who uses drugs living and working in Sweden today. An excellent addition to the literature." -Michelle Addison, Associate Professor of Criminology, Durham University, UK "This is a thought-provoking and intelligent book, brushing aside the negativity which is continually connected with women who use any kind of mind altering substances. Eleonorasdotter is successful in challenging the one-dimensional view of using women as well as in offering a feminist account of the lives of her respondents in the Swedish context. This is a must-read for everyone in the addiction field - users, treaters, researchers, and policymakers." -Elizabeth Ettorre, Professor of Sociology, University of Liverpool, UK. This open access book explores the everyday use of psychoactive substances in contemporary Sweden, focusing on women's use. Drawing on an ethnographic study, it uses critical theory such as queer phenomenology to analyse twelve women's narratives of their use of drugs. The book also draws attention to the social, legal, cultural, embodied and gendered background of drugs and drug use in the contemporary global North, and how the meanings of drug use have shifted over time, with a specific focus on Sweden. It examines topics such as stigma, happiness, children, the body, gifts, the drug market, medication, sickness and health by directing attention to the women's orientations towards objects and people, and how the women align or do not align with social and cultural norms. It discusses how drug-related spaces and directions can be analysed in terms of gender and class, and how, in turn, the directions of contemporary society and culture can be affected by drug use. It speaks to academics in Sociology, Criminology, Ethnology, Anthropology, Gender studies, Law and History. Emma Eleonorasdotter is a researcher and lecturer in Ethnology at Lund University, Sweden. She is an ethnologist and a cultural analyst interested in inequality and everyday lives, and has been part of the editorial team of the Swedish anti-racist cultural magazine Mana since 2008. .